2023
DOI: 10.3390/v15010239
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Pathogenesis, and Serological Characteristics of the Japanese Encephalitis Virus Genotype IV Recent Strain 19CxBa-83-Cv

Abstract: Genotype IV Japanese encephalitis (JE) virus (GIV JEV) is the least common and most neglected genotype in JEV. We evaluated the growth and pathogenic potential of the GIV strain 19CxBa-83-Cv, which was isolated from a mosquito pool in Bali, Indonesia, in 2019, and serological analyses were also conducted. The growth ability of 19CxBa-83-Cv in Vero cells was intermediate between that of the genotype I (GI) strain Mie/41/2002 and the genotype V (GV) strain Muar, whereas 19CxBa-83-Cv and Mie/41/2002 grew faster t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…To investigate virulence, mice were infected with the same titre of virus and observed the progression of disease over 15 days ( Figure 4 (B, C)). Previous studies have indicated that GV JEVs exhibit higher virulence than GIII in mice [ 21 , 26 ]. In our experiments, Mice infected with Muar showed a significant weight loss and higher mortality compared to the GIII Nakayama.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate virulence, mice were infected with the same titre of virus and observed the progression of disease over 15 days ( Figure 4 (B, C)). Previous studies have indicated that GV JEVs exhibit higher virulence than GIII in mice [ 21 , 26 ]. In our experiments, Mice infected with Muar showed a significant weight loss and higher mortality compared to the GIII Nakayama.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly in vitro , differences were observed based on the type of cell line or the virus strain used for comparison. For example, GV strains typically showed similar propagation kinetics to GI and GIII JEVs in most cell lines but exhibited inefficient growth in neuroblastoma cells [ 14 , 26 ]. However, our results indicated that Muar exhibited lower in vitro propagation compared to Nakayama, even in BHK-21 fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to develop treatments for JEV neuropathology are hindered by the difficulties in diagnosing early infection 8 before the virus has infected central nervous system (CNS) neurons; and once the virus has infected CNS neurons, treatments must also be able to effectively enter the brain. In addition, mouse models of JEV neuropathology are often physiologically inappropriate, using intracranial routes of infection or very young mice [9][10][11] . Well-characterized, adult mouse models with high penetrance of JEV neuropathology after peripheral inoculation would represent useful tools to study mechanisms of infection and disease and evaluate potential new interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to develop treatments for JEV neuropathology are hindered by the difficulties in diagnosing early infection (13) before the virus has infected central nervous system (CNS) neurons; and once the virus has infected CNS neurons, treatments must also be able to effectively enter the brain. While a range of JEV mouse models have been reported (Supplementary Table 1) (18), there are no studies of genotype 4 in adult mice, with the only study on genotype 4 JEV using 3-week-old mice (19). Well-characterized, adult mouse models of recent genotype 4 isolates would represent useful tools to study mechanisms of infection and disease and evaluate potential new interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to develop treatments for JEV neuropathology are hindered by the difficulties in diagnosing early infection 13 before the virus has infected central nervous system (CNS) neurons; and once the virus has infected CNS neurons, treatments must also be able to effectively enter the brain. While a range of JEV mouse models have been reported (Supplementary Table 1) 19 , there are no studies of genotype 4 peripheral inoculation in adult mice, with the only studies on genotype 4 JEV using 3-week-old mice 20 or intracranial inoculation 21 . Well-characterized, adult mouse models of recent genotype 4 isolates would represent useful tools to study mechanisms of infection and disease and evaluate potential new interventions.…”
mentioning
confidence: 99%